Green marketing : a new challenge for Romanian organizations - Muntean, Andreea (Array, 2008)
tourism. Environmental improvements can enhance marketability, improve performance, and represent a potent source of innovation. From an organizational standpoint, green marketing means to integrate environmental considerations into all aspects of new touristic product development and marketing. In actual conditions, Romanian touristic companies should prepare to include ecological impact as a part of its marketing strategy. Given current environmental imperatives, they represent the next important stage in corporate environmental management and hence, corporate reputation management. Being "green" is not just a fad, and Romanian companies will have to join the likes of other international firms in preparing marketing strategies to support their sustainability policies. Companies that can prove to consumers and business partners that they are serious about their environmental impact will reinforce their branding. This paper tries to underline how important is for a touristic company to develop sustainable eco - marketing strategy and it proposes some solutions about what Romanian companies should do